Pola Konsumsi Makanan Sumber Asam Lemak Trans pada mahasiswa PTS Kota Bengkulu di Era Pandemi Covid 19 - Halimah Halimah; Nur Elly (Politeknik Kesehatan Kemenkes Bengkulu, 2023)
Obesity is a risk factor for developing Non-Communicable Diseases (NCD). It occurs due to the accumulation of fat resulting from an imbalance between energy intake and expenditure. Changes in the lifestyle of adolescents, who tend to prefer fast food and have limited physical activity, put them at risk of obesity. The development period of Covid-19 gave rise to policies that limited activities and encouraged efforts to improve nutritional intake to minimize the risk of transmission. This study aims to determine the pattern of consumption of food sources containing trans fatty acids among students attending Private Higher Education institutions in Bengkulu City during the Covid-19 pandemic era. Research Method: This study is a survey method as a preliminary investigation into the consumption patterns of food sources containing trans fatty acids among new students of private universities in Bengkulu City during the Covid-19 pandemic. The sample consisted of 40 students, selected using a purposive sampling method. The consumption patterns were assessed using food frequency questionnaires (FFQs) distributed online via Google forms. The data was processed descriptively. Results: The study found a high proportion of consumption frequency in dairy and processed foods, as well as ice cream and beverages. Fried foods also showed a high consumption frequency, including fried tofu and tempeh, fried eggs, bakwan, fish, and fried chicken. Furthermore, products containing high-frequency Hydrogenated Vegetable Oils (HVO) consumed were bread, biscuits, and wafers. Conclusion: The study concludes that processed dairy products, ice cream, and fried foods are consumed frequently among the participants. However, the consumption of vegetables occurs only >3 times per day, with a focus on green vegetables. Future research should delve into the relationship between consumption patterns and adolescent nutritional status and lipid profile. Keywords: consumption frequency, trans fatty acids, adolescents